Why Nursing Students Struggle in Speaking English: Experience, Challenges, And Coping Strategies - Alimah, Nadhira Inas; Suharyanto (Universitas KH. Mukhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2024)
This study aims to determine the implementation, challenges, and strategies of nursing students in improving speaking skills in the English for Nursing classroom. This research utilized descriptive qualitative methods using interviews as a data collection technique. This research addresses nursing students in their second semester at Private Health Universities in Central Java, Indonesia, who are currently enrolled in an English course this semester. The results found that the implementation of speaking activity in the English for nursing classroom was in the form of roleplay. Meanwhile, the topic applied in the activity mostly related to the nursing daily routine in the hospital. The challenges faced by nursing students are the limited English vocabulary and accent barriers that affect pronunciation in speaking English. Students utilize the Google Translate application feature and music as a strategy in overcoming the challenges of improving speaking skills. This study also revealed that the implementation used by lecturers and strategies owned by nursing students are considered to be able to overcome challenges in improving English speaking skills.